A Retrospective Multicenter Study of 1898 Liquefied Petroleum Gas-Related Burn Patients in Eastern China From 2011 to 2015. Issue 6 (30th November 2020) - Jin, Ronghua; Shao, Jiaming; Ho, Jon Kee; Yu, Meirong; Han, Chunmao
Abstract: Liquefied petroleum gas (LPG) is a widely used environment-friendly fuel. Previous studies have shown an increasing number of LPG-related burns. Our study was designed to evaluate the epidemiologic pattern of these injuries and provide recommendations for burn prevention. This retrospective study included all patients with LPG-related burns from eight burn centers in Zhejiang Province, China between 2011 and 2015. Database variables included patient demographics, accident characteristics, and injury characteristics. The association between different categorical variables was identified using the chi-square test. And the association between two or more means of quantitative variables was analyzed by the one-way analysis of variance or t -test. A total of 1898 patients were included, 47.31% were males and 52.69% were females. The predominant age group was 31 to 70 years (74.50%), and the majority were poorly educated and the incidence peaked from June to September. The most common place of occurrence was home (74.08%) and gas leak (96.52%) was the most common cause. The four limbs (43.33%) were the most frequently affected areas; the mean burn area was 25.19 ± 20.97% of the total body surface area and most patients (46.89%) suffered from moderate burns. The mean length of hospital stay was 17.66 ± 16.55 days and the majority of patients (89.36%) recovered with a 0.84% mortality rate. Our findings reflected that the increase in incidence rate was alarming, and the causes resulting in LPG-related burns have not gained much attention yet. Therefore, this calls for simple but strict measures aiming at each hazardous step during the use of LPG to prevent these burn injuries.